2016
DOI: 10.1136/lupus-2016-000169
|View full text |Cite
|
Sign up to set email alerts
|

TAC-TIC use of tacrolimus-based regimens in lupus nephritis

Abstract: Current guidelines do not mention tacrolimus (TAC) as a treatment option and no consensus has been reported on the role of TAC in lupus nephritis (LN). The present study aimed to guide clinical judgement on the use of TAC in patients with LN. A meta-analysis was performed for clinical studies investigating TAC regimens in LN on the basis of treatment target (induction or maintenance), concomitant immunosuppression and quality of the data. 23 clinical studies performed in patients with LN were identified: 6 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
(43 reference statements)
0
26
0
2
Order By: Relevance
“…Our patient was treated with low-dose cyclosporine (3 mg/kg/day) for 12 months without adverse events. On the other hand, tacrolimus, which is another calcineurin inhibitor, is more widely used for SLE than cyclosporine, particularly for those complicated with lupus nephritis [ 24 , 25 ]. However, it is unknown if tacrolimus would also be helpful for SLE-associated MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was treated with low-dose cyclosporine (3 mg/kg/day) for 12 months without adverse events. On the other hand, tacrolimus, which is another calcineurin inhibitor, is more widely used for SLE than cyclosporine, particularly for those complicated with lupus nephritis [ 24 , 25 ]. However, it is unknown if tacrolimus would also be helpful for SLE-associated MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies have suggested that calcineurin inhibitors (CNI, that is, CsA and, mainly, TAC) may have equal or better efficacy than the aforementioned ‘first-line’ drugs, either when administered alone or as part of a ‘multitarget’ therapy combined with MMF (see ref 47 for a relevant meta-analysis). Moreover, a recent large RCT, including both phases of LN treatment (n=362 and 206 in induction and maintenance phase, respectively), found the combination of TAC with MMF to be superior to CYC in the induction phase (overall response rate at 6 months: 83.5% vs 63.0%, respectively, p<0.001) and equal to AZA for maintenance (similar relapse rate at 18 months: 5.47% vs 7.62%, respectively, with fewer adverse events in the multitarget arm) 48 49.…”
Section: Calcineurin Inhibitors In Ln: Old Drugs New Storymentioning
confidence: 99%
“…We did encounter in one patient with CNI nephrotoxicity, and the patient had significant chronic kidney disease at baseline. A meta‐analysis showed that TAC‐containing regimens were associated with a higher efficacy and less leucopenia, but an increased risk of renal impairment . Voclosporin is a novel CNI with improved pharmacological characteristics that could result in more predictable pharmacokinetics and less variation between patients.…”
Section: Novel Approaches In the Management Of Lupus Nephritismentioning
confidence: 99%
“…A meta-analysis showed that TAC-containing regimens were associated with a higher efficacy and less leucopenia, but an increased risk of renal impairment. 22 Voclosporin is a novel CNI with improved pharmacological characteristics that could result in more predictable pharmacokinetics and less variation between patients. Results from the Phase 2b AURA-LV study (NCT02141672) showed higher response rates with voclosporin compared with placebo, in combination with corticosteroids and MMF, at 24 and 48 weeks.…”
Section: Novel Approaches In the Management Of Lupus Nephritis Tacrolmentioning
confidence: 99%